The effect of digital literacy on student learning outcomes in chemistry learning - Abdul Latip; Nursida Sutantri; Aristo Hardinata (Jurnal Inovasi Pendidikan IPA, 2022)
The study aims to determine the effect of digital literacy levels on learning outcomes of eleven-grade students in chemistry learning with a distance learning system during pandemic Covid-19. This study used a quantitative descriptive method with 74 students as a sample who took chemistry learning. The digital literacy level of students was determined through digital literacy instruments. Meanwhile, students' chemistry learning outcomes consisted of the results of daily tests on buffer solution and solubility product chapter. Based on the results, the digital literacy level of students consisted of 57% of students in the high category, 43% of students in the medium category, and no students in the low category. The results of the Mann-Whitney test between groups of students with high and medium category obtained the following results: 1) there is a significant difference in learning outcomes in the buffer solution chapter between students with high and medium digital literacy levels (p= 0.003), 2) there is a significant difference in learning outcomes in the solubility product chapter between students with high and medium digital literacy levels (p= 0.001). These results indicate that the students’ digital literacy level has a significant effect on students’ learning outcomes in chemistry distance learning.